344 Protein supplementation during gestation enhances offspring growth performance of Wagyu sired but not Angus sired cattle. (5th December 2019) - Moffitt-Hemmer, Natasha; Liu, Xiangdong; Deavilla, Jeanene; Neibergs, Shannon; Busboom, Jan; Nelson, Mark; Du, Min
Abstract: Wheat straw based diets are commonly fed to pregnant cows in Pacific Northwest, which may not meet protein requirements, but its impact on growth performance of offspring is unclear. Angus is the most common breed in this region while Wagyu is gaining popularity due to enhanced meat quality. The interaction between maternal nutrition and breed on growth performance of calves was examined. Angus cross cows (621 ± 73kg) were selected and randomly allotted to two groups and inseminated with either Angus or Wagyu semen. At 185 days of pregnancy, cows in each group were further separated into two-subgroups: control diet (CON, n = 21) received 85 % of the NRC metabolizable protein requirement, and protein supplemented group (SUPP, n = 21) received 108 % of requirement until calving. Then, cows and calves were moved to pastures and the cow calf pairs grazed rangeland. After weaning, calves were backgrounded, finished, and harvested at a body weight of 576.5 ± 16.6 kg. There were no differences between CON and SUPP in birth weight. However, SUPP increased 205 days adjusted weaning weight of Wagyu progeny (P < 0.01) and average daily gain (ADG) during the period of birth to weaning (P < 0.05) compared to calves from cows fed the CON diet. Moreover, Angus progeny had higher 205 days adjusted weaning weight (P < 0.01) and ADG during birth to weaning than Wagyu fed SUPP diet (P = 0.056). In both treatments, Angus gained weight faster and showed higher weight before finishing than Wagyu (P < 0.05). Angus had higher harvest weight (P < 0.01) and maternal protein supplementation tended to increase the dressing percent (P = 0.06). In conclusion, maternal protein supplementation enhanced growth performance of Wagyu but not Angus cattle, and Angus grew faster than Wagyu sired cattle. (Supported by USDA-NIFA grants 2015-67015-23219/2016-68006-24634 to MD)